ANALYSIS OF THE INCIDENCE OF CHILDREN WITH APPENDICITIS - Farmonova , Rukhshona Farrukhovna; Akhmedov , Islamjan Yusufjanovich (Educational Research in Universal Sciences, 2024)
Appendicitis is the most common surgical disease of the gastrointestinal system and one of the most dangerous diseases. During life, a person has a very high probability of getting acute appendicitis. Appendicitis is an inflammation of the appendix, a worm-like tumor located in the lower part of the intestine. It starts from the cecum, gradually narrows and has no way out.